USAHA GURU PAI DALAM MENGEMBANGKAN MEDIA PEMBELAJARAN PADA MASA PANDEMI DI SMP DARUL ULUM WARU- SIDOARJO - Maftuh Maftuh; Firda Hafidhoh (JP : JURNAL PENDIDIKAN, 2021)
Abstract: Learning media is tool or something that can facilitate the implementation of learning. Media is needed and becomes a stimulus for successful learning. Like a doctor without medical equipment in this pandemic period is none other than using android-based learning media. Because there is no face to face and as a form of effort to prevent the spread of covid. With this distance learning, PAI teachers think hard again in preparing lesson plans. What strategies and techniques to do during online learning. This study uses a descriptive qualitative approach, with data analysis using data reduction, data presentation and conclusion drawing, so that the data obtained will produce descriptive data that is natural, as for the data collection techniques using interviews, observation and documentation, for validity The data uses triangulation with source, technique and time. The results of the study show that the Darul Ulum Junior High the PAI teacher’s effort in developing learning media were by compiling lesson plans, attending teacher training. Teacher innovation and creation as well as online class management by making games, online class rules and assignments from google. Keep in order to develop student literacy culture. The media used include. 1. WhatsApp 2. Zoom. As for the supporting factors: infrastructure, parental support, environment and teacher attention. The obstacles experienced include: infrastructure and class facilities that are not conducive.Keyword: Learning Media development, Pandemic Covid